Peridynamics for the Solution of the Steady State Heat Conduction Problem in Plates with Insulated Cracks - Mehmet Dördüncü (Havacılık ve Uzay Teknolojileri Dergisi, 2019)
This paper presents the steady-state heat conduction analysis in plates with insulated cracks using peridynamic differential operator (PDDO). The PDDO converts the local differentiation to nonlocal integration. Since the PDDO permits differentiation through integration, the equilibrium equations remain valid in the presence of discontinuities such as cracks. The governing equations of the steady state heat equation and boundary conditions were solved by employing the PDDO. The robustness of the PDDO was assessed by considering a plate without cracks under different boundary conditions. The influence of the insulated cracks on the temperature and heat flux distributions was investigated. It was observed that heat flux concentrations developed in the vicinity of the crack tips.